Self-Organizing Nanovectors for Drug Delivery - Matricardi, Pietro (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nanomedicine represents one of the most investigated areas in the last two decades in the field of pharmaceutics. Several nanovectors have been developed and a growing number of products have been approved. It is well known that many biomaterials are able to self-organize under controlled conditions giving rise nanostructures. Polymers, lipids, inorganic materials, peptides and proteins, and surfactants are examples of such biomaterials and the self-assembling property can be exploited to design nanovectors that are useful for drug delivery. The self-organization of nanostructures is an attractive approach to preparing nanovectors, avoiding complex and high-energy-consuming preparation methods, and, in some cases, facilitating drug loading procedures. Moreover, preparations based on these biocompatible and pharmaceutical grade biomaterials allow an easy transfer from the lab to the industrial scale. This book reports ten different works, and a review, aiming to cover multiple strategies and pharmaceutical applications in the field of self-organizing nanovectors for drug delivery.